Political Openings: Class Struggle During and After the Pandemic. (February 2021) - Gindin, Sam
Capitalism's sustained failures to address popular needs, hopes, and fears have led to a delegitimation of state institutions and mainstream political parties. The crisis is consequently not primarily economic but social and political. The pandemic further exposed capitalism's social irrationalities, intimated how unprepared we were for the much larger environmental pandemic to come, and generated a new level of empathy for the value of frontline workers and the workplace health risks they are exposed to. Building on these openings requires identifying a few key demands around which to unify fragmented social movements; acquiring new understandings; placing larger issues of property rights and democracy on the agenda; and creating workplace, local, and national organizations with the capacity to realize substantive change. The strategic demands the article suggests and elaborates are an emergency wealth tax, conversion of industrial capacity for environmental reconstruction, and the strengthening of unions as a social force.